Análise de indicadores clínicos e epidemiológicos em pacientes com diagnóstico de tuberculose - Fernandes, Marcela de Araujo (2021)
Introduction: Despite being a curable and treatable disease preferably in primary care, tuberculosis continues to be responsible for a large number of hospital admissions and generates big economic impacts to public services. Furthermore, hospitalization for tuberculosis presents high mortality rates compared to outpatient services. Objective: To analyze the clinical and epidemiological indicators of patients who were hospitalized with tuberculosis at a University Hospital in the state of Paraíba-Brazil. Methodology: It is an analytical, exploratory study of a historical series with a quantitative approach, based on secondary data from patient's medical records. Data from medical records of patients who were hospitalized at a University Hospital in the state of Paraíba from January 2008 to December 2018 with a diagnosis of tuberculosis were used. The study population was composed by 416 medical records of patients who were hospitalized with tuberculosis during the study period. The sample was defined after the application of exclusion criteria, totaling 250 medical records. The study was composed by two articles, in order to contemplate the objectives of both, it was necessary to use two samples. For article 1, the type of disease outcome of each patient was verified through the database of the State Health Department of Paraíba, and those who had the outcome "cure" or "death from tuberculosis" were included in the sample, totaling 98 medical records. For article 2, the total number of records from the initial sample (250 records) was used. Analyzes were conducted using the IBM SPSS Statistics version 20.0 software. Initially, descriptive analysis was performed. Bivariate analysis was taken using Pearson's chi-square test (or Fisher's exact test when appropriate) to determine the association between the outcome and the independent variables. Trend analysis was also used, through the creation of polynomial regression models. Results: There was a statistically significant association between the situation of closure (cure or death from tuberculosis), type of entry (p = 0,013), diseases and associated injuries (p = 0,049) and chest X-ray (p = 0,023). The highest incidence of tuberculosis in the studied population, according to each year of observation, was recorded in 2015 (74,70) and the lowest in 2009 (6,90). It was found that the incidence varied over the years and was significant over time (R² = 0,802; p = 0,002), predominantly characterized as increasing, although not constant. Final considerations: The findings pointed the need for greater adherence to tuberculosis treatment in order to reduce the number of cases of abandonment, and the presence of diseases and injuries should be taken into account in the planning of treatment for people with tuberculosis. Furthermore, health surveillance actions should also focus on primary care, focusing on early diagnosis, bonding with the patient and support for adherence to treatment, enabling more control of the disease and consequent reduction in hospital admission rates.